Relation Between Building Envelope and the Operational Period of Heating Systems - Manioğlu, Gülten; Yilmaz, Zerrin (Informa UK Limited, 2006)
The aim of this paper is the determination of the building envelope in relation to the other design parameters by taking the operational period of the heating system into account from the standpoint of providing bioclimatic comfort conditions and energy conservation. An approach is proposed for the determination of the heating performance of the building envelope in relation to the heating period of the system. This approach is applied to a primary school building heated intermittently in Ankara. Different building envelope alternatives are compared with different heating periods and convenient combinations are determined.